Synergistic bactericidal effects of carvone and β-lactams against Xanthomonas campestris pv. vesicatoria - Jeong Yoon Kim; Ju Yeon Kim; Jae Yeon Park; Jin-Seong Kim; Min-Kyung Seo; Min-Kyoung Shin; Jin-Hyo Kim (Applied Biological Chemistry, 2023)
Abstract Xanthomonas campestris pv. vesicatoria (Xcv) causes brown spots on the leaves, stems, and fruits of plants, called bacterial leaf scorch (BLS). For the control of pathogens, antibiotics have been used frequently, and they can develop the resistance. In this study, the bactericidal and synergistic effects of caraway oil and its main components against the pathogen (Xcv) were investigated. The tested caraway oil consisted of 58.4% of carvone and 31.1% of limonene. The minimum inhibitory concentration (MIC) of caraway oil and carvone was the same as 125 μg mL−1, and the minimum bactericidal concentration (MBC) was 1000 μg mL−1 for caraway oil and 500 μg mL−1 for carvone, while limonene showed no inhibition below 1000 μg ml−1. In the growth of Xcv, carvone treatment over 31.3 μg mL−1 inhibited dose-dependently, and the bactericidal effect showed after 18 h more than 250 μg mL−1; It was agreed with the release of intracellular components over 250 μg mL−1, especially. Furthermore, carvone damaged the plasmid DNA of Xcv, and it would be the reason for the bactericidal activity. The synergistic effect of carvone was found with β-lactams selectively; the fractional inhibitory concentration (FIC) indexes of carvone with ampicillin or amoxicillin were below 0.5, and the mixture of carvone (125 μg mL−1) and ampicillin (500 μg mL−1) showed the bactericidal activity as well.